In Search of the Creative Accountants: An Investigation of Creativity Variation in Regional Accounting Firms - Kirsty Meredith; Peter Baxter; Sajid Anwar (Australasian Accounting, Business and Finance Journal, 2022)
Creativity in accounting has traditionally been perceived negatively; however, with rapid technological advances and globalisation, creativity is increasingly being identified as a necessary skill for the profession. The purpose of this study was to investigate whether the creativity levels of individual accountants and perceptions of their creativity varied across different hierarchical levels and service areas in regional accounting firms. A survey was conducted of professional accountants working in regional Australian accounting firms. Responses were analysed using Multivariate Analysis of Variance. This study found that accountants’ creativity and accountants’ perceptions of the importance of creativity are significantly related to their perceptions of firm culture; and these relationships are, to some extent, moderated by the hierarchal level of the accountants. This study highlights that to facilitate creativity, accounting firm managers must consider the organisational culture that exists within their firms, and how their higher-level accountants can be involved in facilitating desired cultural shifts. Weak or no evidence was found to support the effects of service area on accountant’s creativity and perceptions of creativity.
Keywords: Creativity; Accounting; Organisational culture; Regional Australia